Imported foods : microbiological issues and challenges - Doyle, Michael P., 1949-; Erickson, Marilyn C. (Emerging issues in food safety., 2008)
Food safety concerns have become a crucial public health issue. Perhaps most alarming of these is the questionable safety of many imported foods. As the market for food becomes increasingly global and our population clamors for more fresh produce and uncooked ready-to-eat foods, the microbiological risks of imported food have dramatically increased. This volume describes the problems with imported foods and suggests specific programs to improve the monitoring and safety of imported foods.